Screening for lead exposure in children in Belize - Charalambous, Andreas; Demoliou, Katie; Mendez, Marco A L; Coye, Robert B.; Solorzano, Giovanni; Papanastasiou, Elena C. (My University, 2009)
Objectives. The objectives of this pilot study were to determine the blood lead levels in children in Belize and to try to relate these findings to demographic variables. Methods. With permission from parents, capillary blood was collected from the fingers of 164 children with an age range of 2 to 8 years, living and attending school in the spring of 2002 in four towns: Belize City, San Pedro, Orange Walk, and Benque Viejo. The sample represents 0.4% of all children in Belize in that age range. Lead levels were analyzed by the method of anodic stripping voltammetry using the ESA LeadCare analyzer. Results. The mean blood lead level for the children in the sample was 4.94 micrograms per deciliter (μg/dL) with a standard deviation of 2.46. However, 11 children (7%) had blood lead in the range of 10.1-13.8 μg/dL, which is the level of concern according to guidelines of the Centers for Disease Control and Prevention. Children living in the large urban centers of Belize City and Orange Walk town had higher lead levels (mean 5.80 and 5.74 μg/dL) than children living in the smaller towns of Benque Viejo and San Pedro (mean 4.17 and 4.63 μg/dL). There were no statistically significant differences between male and female children. Conclusions. These data indicate that children in Belize are being exposed to lead and suggest that this pilot study be followed up with a comprehensive study with a larger sample and correlation of the findings to socioeconomic characteristics, to children's behavior, and to the home and school environment.
Keywords: Lead; Mass screening; Belize